2011
DOI: 10.1007/s10612-011-9147-7
|View full text |Cite
|
Sign up to set email alerts
|

Do Retributive and Restorative Justice Processes Address Different Symbolic Concerns?

Abstract: In support of a unitary conceptualization of retributive justice (justice through the imposition of punishment) and restorative justice (justice through dialogue aimed at consensus), three studies using hypothetical and recalled experiences of victimization found that people's endorsement of, and satisfaction with, either justice notion depends on the symbolic meaning of the transgression. In Study 1, perceiving the transgression as a status/power violation was uniquely related to the endorsement of retributiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Consistent with this, retribution is often measured as a mix of items capturing some of these dimensions (e.g. Okimoto, Wenzel, & Feather, 2011;Orth, 2003;Wenzel, Okimoto, & Cameron, 2012).…”
Section: Punishment Goalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Consistent with this, retribution is often measured as a mix of items capturing some of these dimensions (e.g. Okimoto, Wenzel, & Feather, 2011;Orth, 2003;Wenzel, Okimoto, & Cameron, 2012).…”
Section: Punishment Goalsmentioning
confidence: 98%
“…Punishment symbolically labels the offence as wrong, thereby restoring people's faith in shared values. Importantly, both status/power (Okimoto et al, 2011;Wenzel & Thielmann, 2006;Wenzel et al, 2012) and value (Okimoto et al, 2011;Vidmar, 2000;Wenzel et al, 2012) restoration motives have consistently been found to relate to retributive responses to crime. In our study, we hypothesise that:…”
Section: This Researchmentioning
confidence: 99%
“…Transgression victims prefer the use of restorative procedures to more punitive approaches when they share an identity with the offender and/or desire to establish consensus about the violated value (e.g., Wenzel et al 2012;Wenzel et al 2008Wenzel et al , 2010. And, people have lessened negative emotional experiences and calmer physiological reactions with restorative, as compared to retributive, responses to imagined transgressions against them (Witvliet et al 2008).…”
Section: Restorative Justice and Its Benefits For Victimsmentioning
confidence: 99%
“…Through this lens, truancy or 'unexplained school absenteeism' (Kearney, 2008b) is an expression of a weak belief about the importance of going to school. Establishing a shared belief through the application of restorative process becomes the initial step for taking on the responsibility to address truancy (see Drewery, 2004;Okimoto et al, 2009;Wenzel et al, 2012). At the ASEP conference, the process begins with the ASEP participants sharing their perspectives on why there is a truancy problem.…”
Section: Discussionmentioning
confidence: 99%
“…The restorative process is theorised to establish a shared concern among the conference participants about the problem behaviour and motivate the group to work together alongside the person who displays the behaviour towards change (Drewery, 2004;Wenzel, Okimoto, & Cameron, 2012). According to the theory of TPP, police mobilises a third party's legal powers, in this case, the school's, to increase deterrence of delinquency and raise awareness of legal responsibilities , Mazerolle & Ransley, 2006.…”
Section: The Asep Conferencementioning
confidence: 99%